Design, synthesis and biological evaluation of caffeoyl benzanilides as dual inhibitors of HIV integrase and CCR512. Issue 10 (17th August 2016) - Sun, Xuefeng; Fan, Ningning; Xu, Weisi; Sun, Yixing; Xie, Xin; Guo, Ying; Ma, Liying; Liu, Junyi; Wang, Xiaowei
Abstract : Novel series of caffeoyl benzanilides have been synthesized and evaluated as dual inhibitors of HIV-1 CCR5/IN. Compound9a exhibited the possibility of being a dual inhibitor of HIV-1. Abstract : Novel series of caffeoyl benzanilide compounds as dual inhibitors of HIV-1 CCR5/IN were designed and synthesized. The biological results indicated that the acetylated compounds with double bonds were reduced, especially compound9a, which showed potential activity against HIV-1 CCR5 tropic viruses with an EC50 value of 4.85 μM, as well as binding affinity with IN ( K D 2.4 μM). Molecular modeling studies also suggested the possible binding mode of9a with CCR5 and IN. These results indicated that9a has the possibility of being a dual inhibitor of HIV-1.